SOLUBLE EXPRESSION OF SYNTHETIC CSF3syn GENE FUSED WITH THIOREDOXIN IN Escherichia coli BL21(DE3) THROUGH AUTOINDUCTION METHOD AND PURIFICATION - Riyona Desvy Pratiwi; Asrul Muhamad Fuad (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2015)
A synthetic human gene of CSF3 (CSF3syn.Ec3), coding for hG-CSF was succesfully subcloned into pET32a(+) expression vector and fused with thioredoxin (Trx) at its N-terminal as fusion partner. The obtained fusion gene of Trx-CSF3syn within the recombinant plasmid pET32a(+)_CSF3yn.Ec3 was verified by PCR, plasmid restriction, and DNA sequencing analysis. In order to investigate the fusion gene expression, we transformed Escherichia coli BL21(DE3) as the host with the recombinant plasmid. The gene was succesfully expressed within the cytosol as fusion protein of Trx·tag, His·tag, S·tag, EK-site, and hG-CSF moities. By the autoinduction method, it was obtained 49% from the soluble fraction and 51% from the insoluble fraction. The soluble fraction was subsequently purified by IMAC method (Ni-NTA) and characterized.Key words : hG-CSF, thioredoxin, autoinduction, IMAC, E.coli.